Elevating the Pre-service Teacher's Translation Skill based on Learner Autonomy - Rafiqa Rafiqa; Sukmawati Yasim (EDUVELOP, 2019)
This paper attempts to improve the pre-service teachers based on student's learner Autonomy. The EFL classroom by first describing the role of translation in EFL learning, then exploring Learner Autonomy can be regarded as an effective teaching method to elevate student's Translation skill. Research setting at West-Sulawesi University, Majene West Sulawesi. The method was used pre-experimental design by one group pretest and posttest. Over 22 students programming Translation were the samples of this study by using purposive sampling technique. To collect the data, researchers used translation test as instrument, it was applied on pretest and posttest. To improve student's skill towards Translation, Learner Autonomy was implemented for 12 meetings within 4 months. The notion of learner independence or learner autonomy moves into an area where learners can direct their own learning particularly in translating the sentences and text provided during the class. It could mean those learning activities which take place without the immediate intervention of the teacher. In this scenario, learners set their own objectives and follow strategies devised by them to fulfill them. This is in turn facilitates the learner to become more efficient and effective when they study independently. Learners are compelled to assume responsibility for their own learning. The result of this study was Learner Autonomy successfully elevated the pre-service teacher's Translation.